AI-Based Ventilation KPI Using Embedded IOT Devices - Nikita Pawar; Arti Devkar; Arti Nagare; Prof. Salunkhe S.V; Dr. Divekar S.N (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The integration of Artificial Intelligence (AI) with Internet of Things (IoT) devices presents a transformative approach to enhancing ventilation systems in smart environments. This paper proposes an AI-based ventilation Key Performance Indicator (KPI) model using embedded IoT devices, aiming to optimize air quality, energy efficiency, and overall system performance in real-time. The system leverages IoT sensors to collect data on temperature, humidity, CO2 levels, and airflow, which is then processed by AI algorithms to provide actionable insights into the efficiency and effectiveness of the ventilation process. By continuously monitoring environmental conditions, the AI model can predict and adjust the ventilation settings, ensuring a balance between comfort and energy consumption. The implementation of such a system can significantly contribute to energy savings, improved indoor air quality, and smarter building management, making it a crucial component in the development of smart cities and energy-efficient infrastructure.